2016
DOI: 10.1049/iet-epa.2015.0309
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic vibration noise analysis of transformer windings and core

Abstract: Analyses of transformer electromagnetic vibration noise are presented in this study. A finite element model is established which combines transient electromagnetic field analysis, mechanical field analysis and acoustic analysis to calculate the sound pressure level of the radiated noise around the transformer. Transient electromagnetic field analysis is performed to get the Lorentz, reluctance magnetic forces and magnetostriction according to Maxwell theory and virtual displacement principle. Mutual influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 21 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Therefore, rather than use the simple mass-spring analysis, we proposed a numerical simulation using a 3D model [10]. Some other papers also proposed 3D model simulations of the transformer noise [11] [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rather than use the simple mass-spring analysis, we proposed a numerical simulation using a 3D model [10]. Some other papers also proposed 3D model simulations of the transformer noise [11] [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…In [12] and [13], the cores, the winding coils, the insulation oil, and the tank were analyzed using a 3D solid FEM model, so a huge number of model elements would have to be calculated for regular routine works of small core-form transformers..…”
Section: Introductionmentioning
confidence: 99%
“…This study showed the relationship between total harmonic distortion (THD) and the change in load noise but did not predict the load noise. On the other hand, electromagnetic, structural, and acoustic analyses of noise, considering the windings and cores of transformers are shown in [6], [7] by applying 3-dimensional finite element analysis . This method may provide accurate predictions of load noise, but it is difficult to expect results in a short time because its pre-processing and computing times are relatively long.…”
Section: Introductionmentioning
confidence: 99%
“…Noise is an inherent characteristic of transformers that cannot be totally eliminated due to the vibrations produced in their core by the magnetostriction effect [14,15], and in the winding by the effects of leakage flux [16][17][18][19]. Consequently, it is necessary to verify the product in accordance to the audible noise limits.…”
Section: Introductionmentioning
confidence: 99%